Pertimbangan Hakim Tentang Pilihan Denda Sebagai Pemidanaan Pada Tindak Pidana Dalam KUHP : Studi Kasus Putusan No. 368/Pid.B/2015/PN.Kbj dan Putusan No. 299/Pid/2016/PT.Md - Fhytta Imelda Sipayung; Syafruddin Kalo; Muhammad Hamdan; Muhammad Ekaputra (Universitas Sumatera Utara, 2019)
Abstract. Imprisonment was not always give effect deterrent means a convict, but the choice of imprisonment remains a Prima Donna and a popular choice for law enforcers, especially when the judge drop the verdict against the accused in the the trial. Despite the undeniable imprisonment is not the only option pemidanaan in the Criminal Code (Kitab Undang-Undang criminal law) which is positive law in Indonesia. There are other pemidanaan option should be used a law enforcement, criminal one is fine. Problems in the study is how the consideration of judges in criminal fines disconnected contained in criminal cases, how the criminal fines in the context of the criminal law and pemidanaan and how the application of criminal sanctions against the perpetrators criminal actions contained in the ruling criminal Number 368/Pid. B/2015/PN. KBJ and verdict Number 299/Pid/2016/PT. Mdn). Shove off from the problem, which is the purpose of this research is to know at once discover what into consideration judges in criminal fines disconnected contained in criminal cases, to know how the criminal fines in the context of criminal law and pemidanaan, as well as find out and analyze how the application of criminal sanctions against the perpetrators of the criminal act contained in the ruling criminal Number 368/Pid. B/2015/PN. KBJ and verdict Number 299/Pid/2016/PT. Mdn). We in this study are normative, law then principal data in this research is the primary data. Data collection is carried out by means of research libraries. As for the results of this research is the State Court judge that checks Kabanjahe and break the criminal Number 368/Pid. B/2015/PN. KBJ on behalf of defendant Relta Br. Tarigan dropping criminal fines against the defendant a number of Rp 2. 500,000,-(two million five hundred thousand dollars) and provisions when the fines are not paid changed with criminal confinement for 6 (six) months, where the verdict dropped based on Article 351 (1) of the CRIMINAL CODE, the number 2 year 2012 Perma, book Statute of the law of criminal procedure (CODE of CRIMINAL PROCEDURE) number 8 Year 1981 as well as other legal provisions concerned. Upon the verdict, the Prosecutor proposed the remedy of appeal. The difference in the view of the consideration of the Tribunal judges in the first instance and appellate Judge of the Tribunal in the High Court of Medan with Verdict Number 299/Pid/2016/PT. Mdn, just about the inclusion of Perma number 2 Year 2012 On the adjustment of the Limitation Criminal acts of light and the amount of the fine in the criminal code, but the Tribunal judges in the Appeal at the High Court of Medan still concurred the Tribunal Judges District Court with criminal dropping Kabanjahe fines against the defendant as the perpetrator of the the crime of persecution. Keywords: consideration of the judge, fines, criminal act, criminal code.